(untitled) (Bulletin of criminological association of Ukraine, 2023)
The relevance of this article is in the fact that current trends in the process of democratization and humanization of criminal proceedings require a different rethinking of the essence of the basic categories of criminal procedure, including the principles of criminal proceedings. Consideration of the scientific approaches to the interpretation of publicity of criminal procedure allowed the author to form his own point of view on its understanding. It is determined that the scope of the publicity of criminal proceedings should extend to all participants to criminal proceedings, in particular, regardless of their affiliation with public authorities and officials.